Plantas hortícolas dos quintais e sua importância para as famílias do assentamento Pirituba II , Itapeva/Itaberá,SP - Galvão, Aline Carolina [UNESP] (2014)
The present study aimed to verifying the importance of homegardens to ensure food security and household income in Pirituba II Setlement. 30 farmers were interviewed in their homegardens and analyzed the data deliveries to the Food Purchase Program (PAA in Portuguese) of the cooperative that respondents participate. The homegardens were irregularly structured with area averaging 17,933 m 2 . All homegardens are associated with the animal component, most (89%) poultry. 81 plant species were found, of which 63 genera divided into 37 botanical families. On average, each home garden had 13 varieties considered as food, the smallest quantity of plants in a yard was 7 and 30 the biggest edible cultivated plants belonging to Cuc urbitaceae, Rutaceae and Brassicacea belong. The most species are produced fruit plants (35.9%), followed by vegetables (27.2%) and broadleaves (17.4%), on a smaller scale are annual (7.6%) and others (12%) . Regarding the growth habit of the species, 50% are herbaceous plants, 26% arboreal, 11% creeping, 10% shrubby and 3% vine. The cultural practices within these spaces agroecological, ensuring the balance of the system. The management of these gar dens are made by family members. Families have great dependence on external inputs, mainly seeds and seedlings. A high degree of knowledge about the uses of resources was observed. This collaborates agrobiodiversity conservation of food security and natu ral resources of the family and are a source of income with supplies for the Food Purchase Program